A Potential Role of the Curry Spice Curcumin in Alzheimer's Disease - Ringman, John M.; Frautschy, Sally A.; Cole, Gregory M.; Masterman, Donna L.; Cummings, Jeffrey L. (Current Alzheimer Research, 2005)
There is substantial in-vitro data indicating that curcumin has antioxidant, anti-inflammatory, and anti-amyloid activity. In addition, studies in animal models of Alzheimer's disease (AD) indicate a direct effect of curcumin in decreasing the amyloid pathology of AD. As the widespread use of curcumin as a food additive and relatively small shortterm studies in humans suggest safety, curcumin is a promising agent in the treatment and/or prevention of AD. Nonetheless, important information regarding curcumin bioavailability, safety and tolerability, particularly in an elderly population is lacking. We are therefore performing a study of curcumin in patients with AD to gather this information in addition to data on the effect of curcumin on biomarkers of AD pathology.
Keywords: inflammation